Motor competence in Czech children aged 11-15: What is the incidence of a risk of developmental coordination disorder? - Jakub Kokštejn; Rudolf Psotta; Martin Musálek (Palacký University Olomouc, 2015)
Background: Current findings suggest that the prevalence of developmental coordination disorder (DCD) ranges widely between countries. A major reason for this wide range of prevalence is how cases of DCD are identified. Gender differences in level of motor competence in children with movement difficulties may play a key role in the choice of type of intervention. Objective: The aim of the study was to reveal the prevalence of significant movement difficulties with high probability of presence of DCD in Czech children aged 11 to 15. At the same time we wanted to assess possible gender differences in different types of the movement difficulties. Methods: A total sample of 507 children (age 11-15 years, 262 boys, 245 girls) from all Czech regions was included. The MABC-2 test was used for the identification of movement difficulties with different severity. Children whose total test score (TTS) was ≤ 15th percentile were considered at risk for having DCD (children with rDCD). Children whose TTS was ≤ 5th percentile were considered as having significant movement difficulties with high probability of presence of DCD. An analysis of gender differences of children with rDCD in MABC-2 motor components and tests were carried out. Results: From the entire sample, 33 participants (22 boys, 11 girls) were identified as at risk of having DCD (rDCD). 1.4% of the total sample met the criterion for significant movement difficulties with high probability of presence of DCD. 5.1% of the total sample met the criterion for identification of the risk for having movement difficulties. Almost twice as high predisposition for the occurrence of movement difficulties was revealed in boys as compared to girls in a population of children with rDCD (OR = 1.95, 95% CI: 1.16-2.74). Girls with rDCD performed better in manual dexterity with a medium effect of the gender (Cohen's d = 0.58), whereas boys with rDCD achieved better results in aiming and catching also with a medium effect (Cohen's d = 0.50). Nevertheless, statistically significant differences in these components have not been confirmed. Conclusion: We found a 1.4% incidence of significant movement difficulties among Czech children. A significantly higher incidence of developmentally conditioned movement difficulties were found in boys. Gender differences in the level of motor skills of children with rDCD reflect a common trend in the general child population.